Penerapan Blockchain Dalam Meningkatkan Keamanan Akuntansi Dan Transparansi Sistem Informasi Akuntansi - Zahwa Juwita; Febri Yollanda; Mita Azira; Zul Azmi (GLOBAL SCIENTS PUBLISHER, 2025)
Blockchain technology has enormous potential to transform various sectors including accounting. This article is written to discuss how the application of blockchain technology can improve security and transparency in accounting information systems. This study uses a literature study method with a qualitative approach. The results of the study show that blockchain can improve data integrity, prevent manipulation, and provide transparent access to stakeholders. However, obstacles such as implementation costs, regulations, and technology adoption are still challenges that need to be overcome. This article concludes that blockchain has great potential in the world of accounting, if only these challenges can be overcome.